Employee-Owned Firms and the Careers of Young Workers - Gabriel Burdin; Jose Garcia-Louzao (Institute of Labor Economics (IZA), 2023)
Using detailed administrative data from Spain, we investigate the impact of having an initial work experience in an employee-owned firm (EOF) versus a conventional business on subsequent earnings. We find that young workers' exposure to EOFs at the time of labour market entry reduces earnings by about 8% during the first 15 years in the labour market. The selection of individuals with low initial ability in EOFs does not appear to be a relevant channel. Our results seem to be rather related to differences in job mobility and wage returns to experience. On the one hand, we document lower wage returns to experience acquired in EOFs, although no differences in subsequent career progression in terms of promotions. On the other hand, we find that workers who had their first job in EOFs show a strong attachment to such a business model and are less likely to voluntarily leave their employers. Taken together, our findings suggest the existence of non-pecuniary job attributes offered by EOFs that might compensate for lower lifetime earnings.
Keywords: J31; J50; J62; 330; employee-owned firms; careers; wages; job mobility